Strategi Efektif Publikasi Artikel pada Jurnal Internasional Tinjauan Literatur bagi Peneliti Pemula - Miftahul Ilmi; B. Herawan Hayadi; Natis Sutisna; Siti Mahfudhoh; Akhmad Jonny Irawan; Tubagus Mahar Ma'arif (STAI Darul Qalam Tangerang, 2026)
Publishing articles in international journals is an important indicator of academic productivity and research impact. However, many researchers, particularly novice authors, face challenges in the publication process such as selecting appropriate journals, preparing high-quality manuscripts, and understanding the peer review process. This study aims to identify effective strategies to increase the chances of publishing articles in international journals. This research uses a literature review method by analyzing various scholarly sources related to academic publishing practices. The findings show that successful publication depends on several factors including selecting appropriate journals, ensuring strong research methodology, using relevant references, complying with journal guidelines, and responding effectively to reviewers’ comments. The results of this study are expected to serve as a practical guide for researchers in improving the quality of scientific writing and increasing their chances of publishing in reputable international journals.